2019
DOI: 10.3198/jpr2018.09.0058crgs
|View full text |Cite
|
Sign up to set email alerts
|

Registration of BTx623dw5, a New Sorghum Dwarf Mutant

Abstract: The USDA-ARS has released a new dwarf sorghum [Sorghum bicolor (L.) Moench) mutant BTx623 dw5 (Reg. No. GS-787, PI 688506). Dwarf genes have been an important driving force in breeding since the Green Revolution. Single dwarf locus is used to breed high-yielding semidwarf wheat (Triticum aestivum L.) and rice (Oryza sativa L.) cultivars. However, in sorghum, any of the known dwarf loci alone are insuicient to breed semidwarf grain sorghum itting for modern farm practices. Therefore, four dwarf loci have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…So far, three of them have been isolated and cloned: Dw1 (Sobic.009G230800) encodes for a putative membrane protein involved in the regulation of cell proliferation in the internodes (Hilley et al, 2016;Yamaguchi et al, 2016); the product of Dw2 (Sobic.006G067600) is a protein kinase regulating stem internode length; and Dw3 (Sobic.007G163800), which was the first to be identified, encodes a phosphoglycoprotein of the adenosine triphosphatebinding cassette (ABC) transporter superfamily involved in auxin transport, orthologous to maize br2 (Multani et al, 2003). Although Dw1-Dw4 explain most of the observed phenotypic variability for sorghum plant height, the existence of a fifth Dw gene (Dw5) has been recently reported (Chen et al, 2019); additionally, a number of other genes involved in gibberellin and brassinosteroid metabolism have been identified which can directly affect plant height (Ordonio et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…So far, three of them have been isolated and cloned: Dw1 (Sobic.009G230800) encodes for a putative membrane protein involved in the regulation of cell proliferation in the internodes (Hilley et al, 2016;Yamaguchi et al, 2016); the product of Dw2 (Sobic.006G067600) is a protein kinase regulating stem internode length; and Dw3 (Sobic.007G163800), which was the first to be identified, encodes a phosphoglycoprotein of the adenosine triphosphatebinding cassette (ABC) transporter superfamily involved in auxin transport, orthologous to maize br2 (Multani et al, 2003). Although Dw1-Dw4 explain most of the observed phenotypic variability for sorghum plant height, the existence of a fifth Dw gene (Dw5) has been recently reported (Chen et al, 2019); additionally, a number of other genes involved in gibberellin and brassinosteroid metabolism have been identified which can directly affect plant height (Ordonio et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Dw4 has been mapped to chromosome 4 (Li et al, 2015), but the gene behind this locus has not been identified yet. Additionally, a fifth dwarfing locus (Dw5) has recently been reported (Chen et al, 2019).…”
Section: Plant Heightmentioning
confidence: 99%
“…In addition to the wide range of morphological phenotypes, several mutated traits with potential agronomic applications have been isolated from the mutant library. These traits include multiseeded ( msd ) mutants that have panicles with increased seed number and sink capacity (Burow et al., 2014; Dampanaboina et al., 2019; Gladman et al., 2019; Jiao et al., 2018), erect leaf ( erl ) mutants to modify canopy structure (Xin et al., 2015), novel dwarf ( dwf ) mutants for breeding semi‐dwarf varieties (Chen et al., 2019b), brown midrib ( bmr ) mutants for increasing forage and biomass quality (Emendack et al., 2022; Saballos et al., 2012; Sattler et al., 2012, 2014; Scully et al., 2016; Tetreault et al., 2021), and nuclear male sterile mutants ( ms ) for developing novel breeding system (Chen et al., 2019a; Xin et al., 2018, 2017). This resource can help researchers find mutations in their genes of interest online and subsequently characterize the effect of the mutations on the function of those genes.…”
Section: Introductionmentioning
confidence: 99%